Compare of the Frequency of Instrument Fracture of Endodontic File Using Rotary Pro Tapers and HY Flex Series - Aosaf Anwar, Feroze Ali Kalhoro, Mowaffaq Abdullmomen Al Absi, Fozia Rajput, Osama Shaikh, Batool Bibi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of instrument fracture of endodontic file using Rotary Pro Tapers and EDM Hy Flex series. Study Design & Setting: This experimental in vitro study was conducted at Institute of Dentistry Liaquat University of Medical and Health Sciences Jamshoro. Subjects and Methods: Data was prospectively collected from extracted human teeth. A total of 66 canals were included. Simple descriptive statistics were used to present demographic data, along with frequency and percentages to present qualitative variables. It was decided to perform a post-stratification chi square test taking a p-value of less than 0.05 as significant. Results: A total of 66 canals (33 each endodontic file using Rotary Pro Tapers and EDM Hy Flex series) were included. Mean endodontic file in group A and B was 1.28±0.14 mm and 0.58±0.08 mm. Comparison of instrument separation in endodontic file using Rotary Pro Tapers and Hy Flex series showed separation of 09 (27.3%) and 02 (6.1%) respectively. Conclusion: Based on the results of this study, Protaper files generated much more stress than EDM Hy Flex files, but comparisons of instrument separation between the two instruments showed that the latter performed better overall.